Decreased biventricular function following thoracic endovascular aortic repair. (17th December 2019) - Kreibich, Maximilian; Morlock, Julia; Beyersdorf, Friedhelm; Berger, Tim; Allweier, Stephan; Kondov, Stoyan; Pingpoh, Clarence; Czerny, Martin; Siepe, Matthias; Rylski, Bartosz
Abstract: : OBJECTIVES: Preclinical studies have suggested acute stiffening of the aorta following experimental thoracic endovascular aortic repair (TEVAR), resulting in acute elevated pulse pressure, hypertension and possibly heart failure. The aim of this study was to evaluate cardiac remodelling following TEVAR. METHODS: From 2005 to 2018, 519 TEVAR procedures were performed at a single centre. Transthoracic echocardiography was performed pre- and post-TEVAR in 31 patients without previous replacement of the thoracic aorta. Patient characteristics, drug information, radiographic and follow-up data were evaluated. Aortic details were measured in multiplanar reconstruction. RESULTS: Transthoracic echocardiography was performed 2 ± 2 years after TEVAR. At this time, patients received significantly more antihypertensive drugs compared to the pre-TEVAR intake (beta-blocker therapy: P = 0.037; calcium channel blocker: P = 0.022). Compared to pre-TEVAR, there was a significant reduction in the left ventricular ejection fraction ( P = 0.008) and tricuspid annular plane systolic excursion ( P = 0.013) post-TEVAR. A significant increase in the left ventricular mass was not detected in this study ( P = 0.95). The mean distance of 163 ± 66 mm of the descending aorta was covered. CONCLUSIONS: This study suggests negative cardiac remodelling with a decrease in the left and right ventricular function following TEVAR despite an increase in oral antihypertensive medication. The impact of stiffer endovascular grafts compared with the native aortic wall should be considered by endovascular specialists and manufacturers.